Asuhan Keperawatan Maternitas pada Pasien Post Partum Spontan dengan Nyeri Akut Luka Episiotomi: Efektivitas Terapi Sitz Bath - Sofiyati Sofiyati; Cindy Puspanegara (Universitas Muhamadiyah Manado, 2025)
Postpartum is the period after childbirth until six weeks after the delivery of the placenta. Perineal pain often occurs due to spontaneous lacerations or episiotomy, causing discomfort and impaired mobility. Sitz Bath therapy is a non-pharmacological method to reduce pain. Objective: This study aimed to describe nursing care for postpartum patients with episiotomy wounds and to analyze the effectiveness of Sitz Bath therapy in reducing pain. Method: A case study design was used with Mrs. N, a 26-year-old postpartum spontaneous patient with an episiotomy wound. Pain intensity was assessed using the Numeric Rating Scale (NRS) before and after Sitz Bath therapy for three consecutive days. Results: Pain intensity decreased from 4 (moderate pain) to 1 (very mild pain) after three days of intervention. Conclusion: Sitz Bath therapy proved effective in reducing acute pain in postpartum patients with episiotomy wounds and can be implemented in nursing practice.